Factors influencing computer ethics at the workplace: a study of professionals in South-East Asia - Naail Mohammed Kamil, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2014)
The present research is aimed at understanding employees’ perception towards computer use ethic at the workplace. In view of this, the research investigates the extent to which personal characteristics such as gender, religious belief and an employee’s position in the organizational hierarchy can influence his/her attitude towards computer use ethic. The data used for this qualitative research was drawn from in-depth and intensive semi-structured interviews of six prominent professionals; four from the private sector and two from the public sector. Out of the six professionals, there were three males and three females. The study made some interesting revelations; that computer use ethic is one of the greatest concerns for employers which needs to be tactfully addressed through values based orientation rather than compliance or legal based orientation; and as compared to gender and organizational position, religious belief has the greatest impact in guiding and influencing employees towards ethical computer use at the workplace.